Trabalho docente nas calhas dos rios amazônicos: trabalho, interiorização e subjetividade - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The working world in Brazil has undergone a series of transformations in recent decades, bringing teaching work increasingly closer to the demands of the neoliberal market and inserting public higher education into productivist and mercantilist logic. These changes have led to an intensification and precariousness of the teaching work, with direct impacts on the workers, both in their way of working and in their subjectivity. In this process, it is important to consider the particularities of working in small towns in Amazonia and their impacts on the organization of work and subjectivity of university professors. The objective of the study was to analyze the subjective experiences at work of university professors who work in the inner cities of the state of the Amazon through an investigation of ways of life, work organization, experiences of pleasure and suffering, and the use of subjective mobilization by these workers in this Amazonian context. Methodologically, the research is characterized as descriptive with a qualitative approach, using the theoretical framework of Psychodynamic of Work (POW) to analyze the organization of work, the experiences of pleasure-suffering, the mediation strategies, and the health-disease relationship. Ten (10) university professors who work in the countryside of the state of the Amazon participated in the research, and data collection was carried out through individual online interviews. The content of the speeches was systematized from the Analysis of Nucleous Sense (ANS) and the discussion of the results was related to the POW assumptions. The results pointed to a reality in which the ways of life in the Amazon and the organization of work are interrelated, sometimes in contrast, and affect the workers' subjectivity. Although the participants are engaged and manage to use subjective mobilization to overcome the challenges of the work reality, their experiences of suffering are intensified, especially by the overload, the precarious working conditions, and the feelings of devaluation and invisibility, which pose risks to their health. The significance of the work and the students’ roles as points of emancipation and subjectivity transformations were highlighted as crucial aspects of university professors of the countryside.
Teaching work in the channel of the amazonian rivers: work, interiorization and subjectivity
Keywords: Ambiente de trabalho - Corpo docente; Professores - Saúde mental; Professores - Estresse ocupacional; CIENCIAS HUMANAS; Trabalho docente; Subjetividade; Saúde mental; Amazônia